Frequent Activation Delay–Induced Mechanical Dyssynchrony and Dysfunction in the Systemic Right Ventricle - Forsha, Daniel; Risum, Niels; Smith, P. Brian; Kanter, Ronald J.; Samad, Zainab; Barker, Piers; Kisslo, Joseph (Journal of the American Society of Echocardiography, 2016)
Patients with systemic right ventricles frequently experience progressive heart failure and conduction abnormalities leading to abnormal ventricular activation. Activation delay–induced mechanical dyssynchrony can contribute to ventricular failure and is identified by a classic strain pattern of paradoxical opposing wall motion that is an excellent predictor of response to cardiac resynchronization therapy in adults with left bundle branch block. The specific aims of this study were to compare right ventricular (RV) mechanics in an adult systemic right ventricle population versus control subjects, evaluate the feasibility of this RV strain pattern analysis, and determine the frequency of the classic pattern. Young adults (n = 25) with d-transposition of the great arteries, status post Mustard or Senning palliation (TGA-MS), were ambispectively enrolled and compared with healthy young adults (n = 30) who were prospectively enrolled. All subjects were imaged using novel three–apical view (18-segment) RV longitudinal speckle-tracking strain analysis (EchoPAC) and electrocardiographic data. Patients with TGA-MS had diminished RV global peak systolic strain compared with control subjects (−12.0 ± 4.0% vs −23.3 ± 2.3%, P < .001). Most patients with TGA-MS had intrinsic or left ventricular paced right bundle branch block. A classic pattern was present in 11 of 25 subjects (44%), but this pattern would have been missed in four of 11 based only on the RV four-chamber (six-segment) model. Only three subjects underwent cardiac resynchronization therapy. Both subjects who had the classic pattern responded to cardiac resynchronization therapy, whereas the one nonresponder did not have the classic pattern. Systemic right ventricles demonstrated decreased function and increased mechanical dyssynchrony. The classic pattern of activation delay–induced mechanical dyssynchrony was frequently seen in this TGA-MS population and associated with activation delays. This comprehensive RV approach demonstrated incremental value.